Influence of post-cut residue on cut interval, productivity and nutritional quality of BRS Kurumi elephant grass - Jochims, Felipe (2020)
The use of grass species with high productive potential became important to increase the productive index of rural proprieties without increasing production costs. However, materials will only express their full productive potential if handled correctly. Thus, the objective was to evaluate different height removal percentages (40, 50, 60 and 70%) of the initial height pre-indicated for the use of Kurumi grass (80cm) and the effects on the cuts interval, productivity and forage nutritional quality. The most productive height removal was 50%, producing 21 t ha-1 DM, with an average interval between cuts of 18 days in 155 days. This treatment was also superior in the levels of crude protein (18.2%) and organic matter digestibility (79.8%).